Use of fomepizole as an adjunct in the treatment of acetaminophen overdose: a case series. Issue 1 (1st January 2020) - Rampon, Garrett; Wartman, Haley; Osmon, Stephen; Scalzo, Anthony
Abstract: Acetaminophen toxicity remains a leading cause of acute liver failure in the United States and world-wide. Fomepizole is a cytochrome P450 inhibitor that may inhibit production of toxic metabolites of acetaminophen. However there are limited clinical data of its use for this purpose in the literature. Here we present a case series of six patients treated with fomepizole for acute acetaminophen toxicity who sustained no substantial liver injury.